JFK Is a Hypoxia-Inducible Gene That Functions to Promote Breast Carcinogenesis - Yang, Ziran; Zhou, Xuehong; Zheng, Enrun; Wang, Yizhou; Liu, Xinhua; Wang, Yue; Wang, Yanpu; Liu, Zhaofei; Pei, Fei; Zhang, Yue; Ren, Jie; Huang, Yunchao; et al. (Frontiers in Cell and Developmental Biology, 2021)
Many carcinomas feature hypoxia, a condition has long been associated with tumor progression and poor prognosis, as well as resistance to chemoradiotherapy. Here, we report that the F-box protein JFK promotes mammary tumor initiation and progression in MMTV-PyMT murine model of spontaneous breast cancer. We find that JFK is inducible under hypoxic conditions, in which hypoxia-inducible factor HIF-1α binds to and transcriptionally activates JFK in breast cancer cells. Consistently, analysis of public clinical datasets reveals that the mRNA level of JFK is positively correlated with that of HIF-1α in breast cancer. We show that JFK deficiency leads to a decrease in HIF-1α-induced glycolysis in breast cancer and sensitizes hypoxic breast cancer cells to ionizing radiation and chemotherapeutic treatment. These results indicate that JFK is an important player in hypoxic response, supporting the pursuit of JFK as a potential therapeutic target for breast cancer intervention.